TO THE GEOLOGICAL NATURE OF THE SOUTH-WEST PART OF TOMAKIVSKIY GRAVITY MAXIMUM - Pigulevskiy, P. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The analysis of results of several interpretations of the nature of anomaly of a regional Tomakovsky gravitational maximum is made. By results of last complex geophysical researches in structure of earth crust, hypabyssal laccolith of the mantle location in a southwest part of a maximum it is predicted. The prospective total size of a laccolith is from 50 to 70 km. By results of density modelling on a gravitational field and 1D inversion of curves MTS (magnetotellurgic sounding) it is presented by basic and ultrabasic rocks